Digitalize munsell color space for practical application in visual art - Xiao, Yikai (2017)
There are quite a lot of different color models used today. However, the Munsell color system which was developed in the first decade of 20th century is still in wide use. The Munsell color system is quite useful in visual art since it is based on rigorous measurements of human subjects’ visual responses to color. In my current project, my focus is to design and develop a standalone application for Professor Ng Woon Lam and it is aimed to be used as a teaching tool for students to learn the Munsell color space and to analyze artworks from different periods. The development process consists of five major phases: project initial phase, project design phase, project implementation, project testing and evaluation phase. The main development tool for this application is Eclipse (Java IDE) and 3ds Max (3D modelling tool). The application contains two main functions. The first one is based on the 3D model of the Munsell color space, through which the basic information about the Munsell color system will be presented. The other one is to use the mapping algorithm to map the colors appeared in the art pieces to the built model and then use it to analyze the changing of color usage through different art periods. The application developed through the project is quite helpful and useful for the art educators to teach their students. Meanwhile, the algorithm developed and methods used in this project to manipulate the art pieces can be further developed in the visual art industry to find some ways to determine the painting and its produced period.